Pāratitācaṉ pārvaiyil Pārati - Iḷaṅko, Ca. Cu (Aṉṉam, 1982)
Evaluation of the influence of Pāratiyār, 1882-1921, Tamil litterateur and Indian freedom fighter, on the works of Pāratitācaṉ, 1891-1964, Tamil revolutionary poet; includes a selection of poems from Pāratiyār and Pāratitācaṉ